CONCEPTUAL, CONTEXTUAL AND VALUE-BASED FEATURES OF ETHNIC MEDIA IN THE MEDIA SYSTEM OF THE SOUTH OF RUSSIA (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-186-196The article summarizes and categorizes various theoretical and methodological approaches to the concept of ethnic media, as well as analyses their place and role in the system of Russian media and that of the South of Russia in particular. The research reveals such contextual peculiarities of ethnic media as bilingualism, focusing on a specific ethnic community and meeting its needs, as well as creating and maintaining ethnic identity. Among other concepts, the predominant are traditional values, interethnic collaboration and preserving historical memory and culture. The principal values spread by the ethnic media of the South of Russia are interethnic cooperation, language preservation, as well as maintenance of cultural achievements and people’s identity.Key words: regional media, ethnic media, ethnic journalism, ethnic identity, conceptual features, contextual features